2006
DOI: 10.1002/adem.200500164
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Interfacial Moisture Content and Adhesive Fracture Energy of Polymer Coatings on Different Surfaces

Abstract: Sn-Ag-Cu alloy. The Sn-Ag-Cu-Ge alloy solder ball had higher ball shear strength than the Sn-Ag-Cu alloy after an aging test at 150°C. The Sn-Ag-Cu-Ge alloy solder has better characteristics for both thermal oxidation and thermal reliability test. Therefore, it can be concluded that the Sn-Ag-Cu-Ge alloy is a good candidate to solve the oxidation problem, which is the most critical problem of the Pb-free solder. ExperimentalTwo solder ball compositions (in wt%) chosen in this study were : Sn3.0Ag0.5Cu and Sn3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…The chamber used for testing contains water and the sealing surface of the tray is submerged below this level allowing the trays to be tested in an aqueous environment. This is generally observed to degrade an adhesive bond [24]. The burst test also takes into account any areas of poor sealing brought about by the heatsealing technique as the tray will fail at the weakest point along the sealing surface.…”
Section: Adhesion Testingmentioning
confidence: 99%
“…The chamber used for testing contains water and the sealing surface of the tray is submerged below this level allowing the trays to be tested in an aqueous environment. This is generally observed to degrade an adhesive bond [24]. The burst test also takes into account any areas of poor sealing brought about by the heatsealing technique as the tray will fail at the weakest point along the sealing surface.…”
Section: Adhesion Testingmentioning
confidence: 99%
“…This led to the use of silanes that are capable of changing the surface affinity to water vapor [18] without affecting mechanical properties of the materials. Ever since their discovery, silanes have been widely used in the manufacture of composites, and also for various coatings applications [53,54]. Trialkoxysilanes are the most commonly used coupling agents in composite manufacturing due to favorable compatibility with many polymer resins [19].…”
Section: Surface Modificationmentioning
confidence: 99%
“…As water comes in contact with surfaces of hydrophilic or polar materials, the structure of water at the interface differs from the bulk, and interferes with mechanical and chemical behaviors of surfaces and materials (Figure 6a). Therefore, the interfaces in exposure to water or humidity gain significant importance not only to control mechanical and chemical behavior of surface and material, but also to explore new applications [6,54,[80][81][82][83][84][85][86]. Even though understanding of this bound water layer remains incomplete, it has been shown that the changes in structure of water are dominated by hydrogen bond networks and its dynamic evolution [82,[87][88][89].…”
Section: Bound Watermentioning
confidence: 99%
“…Moisture contents can change the surface energy of a substrate that strongly affects the adhesion strength of a coating. 17 Moy and Karasz, 18 Lee and Peppas 19 and Nogueira et al 20 showed that the moisture content on the substrate lowers the glass transition temperature of the coatings that deteriorates film mechanical properties. Wong and Broutman 21 and Xu and Ashbee 22 proved that the moisture contents create cracks or voids in the coatings.…”
Section: Introductionmentioning
confidence: 97%